Differences in risk-adjusted return between conventional and sustainable funds : a study of the swedish fund market - Michaelsson, Adrian; Svensson, Edward (SLU/Dept. of Economics, 2021)
Sustainable investments have received increased interest all over the world amongst institutional and private investors. The number of funds investing in securities according to their ESG characteristics is a constantly growing part of the market. Because of this the in-flow of capital seem to be higher in sustainable funds which might help them counteract their limitations when it comes to risk-adjusted return. Previous studies on the subject have shown inconclusive results on how financial performance is affected by ESG factors. This study therefore aims to find differences between conventional and sustainable funds, in order to see what might affect the risk-adjusted return of funds on the Swedish fund market. The aim of the study is to analyse if it is a difference in yield between sustainable and conventional funds during the market crisis caused by the Coronavirus in order to see how different ESG factors might minimise the total and systematic risk in a portfolio. In total 40 funds were sampled by using a purposive sampling method. The analysis was conducted during a two-year period 2019 to 2020, whereas in 2020 the COVID-19 pandemic started, which set off the market crisis. By using a quantitative study design the funds were analysed with different evaluation models such as Sharpe and Treynor ratios but also with a Wavelet Coherence Analysis. In the study the sustainable funds have experienced a lower systematic risk and a higher risk-adjusted return on average. The Wavelet Coherence Analysis also points to these results as there is a strong coherence between ESG and systematic risk with a negative correlation, i.e. a good Environmental Social Governance (ESG) score provide a lower beta (systematic risk). Differences in risk-adjusted return could be seen between funds profiled differently in the E, S and G segment. The sustainable funds profiled in “S” have performed the best risk-adjusted return, followed by the conventional funds profiled in “G”. The results also suggests that the spread in yield between conventional funds and sustainable funds increases throughout the sample period. Sustainable funds have recovered faster, leading to enhanced risk-adjusted returns both when measured through Sharpe and Treynor ratios. Seemingly, sustainable funds have managed this risk better, by utilising the information more efficiently and reacting to market changes. Therefore, investors can expect sustainable funds to provide a better risk-adjusted return than its conventional peers during a market crisis.